Avoiding Risk, Protecting the “Vulnerable”: A Story of Performative Ethics and Community Research Relationships - Loewen Walker, Rachel; Hartman, Andrew (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
In February 2019, OUTSaskatoon, a 2SLGBTQ+ resource centre in Saskatoon, SK, received 1.1 M in federal funds to support a five-year project set to intervene in the instances and societal perpetuation of gender-based violence toward the 2SLGBTQ+ community. The project involved partnerships between OUTSaskatoon and the University of Saskatchewan, including a comprehensive research and evaluation stream to accompany the delivery of front-line services and educational activities. During the project’s application to the University’s Research Ethics Board (REB), members of the ethics review committee expressed heightened levels of fear and discomfort not only with the subject-matter, but with the role (and centrality) of the community organization within the research process. The documented experience explores pressing barriers to effective and ethical community-university research partnerships. To this end, the authors explore their communications with the REB alongside the themes of “vulnerability,” “risk-aversion,” and more broadly regarding the timelines of community work versus university processes. Together these themes maintain a culture of academic exceptionalism that causes significant barriers to the development of reciprocal partnerships between community partners and universities. In this case, the outcome was hopeful, as a formal complaint to the REB received a documented apology. In documenting this specific, though not unique, experience, we aim to highlight the possibilities for leaning in and building ethical space between and through community and academic environments to foreground both needed critique and collaborative pathways forward.